Peningkatan Ekonomi Melaui Diversifikasi Produk Berbasis Sumber Daya Lokal Pada UKM Sedayu Putri Di Dusun Lokon Rangan Kecamatan Kayangan Kabupaten Lombok Utara - Sulaimiah; Sulhaini (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Community service that aims to increase community income by utilizing the potential around them is carried out on small and micro small businesses in Lokan Rangan hamlet, Kayangan district, North Lombok Regency through product diversification, especially from agricultural and plantation products, namely how to make clothing products using natural dyes derived from the bark and roots of existing tree roots. Sedayu Putri is trying to increase their income by creating ecobrik batik material, which is an environmentally friendly material. They also target sales to the upper economic class as the main clothing material in addition to the community around the service location, even can be used by outsiders or far from the local area. Starting from producing by looking for quality material inputs, then the production process that is handled by skilled employees, drawing interesting motifs as well as coloring that suits consumer tastes, attractive packaging